Radiation protection for surgeons and anesthetists: practices and knowledge before and after training. (8th January 2018) - Brun, A; Mor, R Alcaraz; Bourrelly, M; Dalivoust, G; Gazazian, G; Boufercha, R; Lehucher-Michel, M P; Sari-Minodier, I
Abstract: The use of radiological activity in the operating room (OR) and a regulatory decrease of the eye lens dose warrant an assessment of how medical staff are protected from radiation. This study aims to evaluate practices and knowledge in radiation protection (RP) for OR doctors before and after training. A descriptive study of surgeons and anesthetists in a French public hospital center was conducted in 2016. An ad hoc questionnaire concerning occupational practices and knowledge about RP was distributed before and one month after RP training. Among 103 doctors attending the training, 90 answered the questionnaire before the training. Results showed a lack of knowledge and good practice in RP. Most of the participants (86.7%) had never been trained in RP and recognized insufficient knowledge. Most of them (92.2%) wore a lead apron, 50.0% a thyroid-shield, 5.6% lead glasses, 53.3% a passive dosimeter and 17.8% an electronic dosimeter. None of them benefitted from collective protective equipment such as a ceiling suspended screen. The questionnaire following the training was completed by only 35 doctors. A comparison before and after training results showed an improvement in knowledge (scores of correct responses: 5.5/16 before and 9.5/16 after training) but not in RP good practices (scores of correct responses: 3.2/7 before and 3.3/7 after training). One training session appears to be insufficient to improve the application of the safety rules when x-rays are used. Communication needs to be improved regarding RP among anesthetists and surgeons, such as training renewal, workstation analysis in OR related to x-ray use and occupational medical follow-up. Otherwise, radiological risks in OR need to be given better consideration, such as radio-induced cataract risk. It is necessary to encourage the use of dosimeters and protective equipment and to strengthen access to lead glasses and collective protective equipment, such as ceiling suspended screens. All these recommendations ensure the received dose is reduced to as low as is reasonably achievable.